2021
DOI: 10.1111/1346-8138.15953
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric psoriasis induced by HLA‐B46‐Cw1 haplotype: A retrospective study of psoriasis onset after hematopoietic stem cell transplantation

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by raised, well-demarcated, erythematous plaques and can significantly impair a patient's quality of life. 1,2 Recent advances in genetic analysis technology have revealed the contribution of the HLA-C locus to psoriasis. 3,4 Along with loci relating to the major histocompatibility complex (MHC), genome-wide association studies (GWAS) for psoriasis and psoriatic arthritis have revealed loci relating to immunological genes. Thus, psoriasis develops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The genetic backgrounds including HLA were not assessed. 20 There were no data of serum level of TNF and of anti-IFX antibody to speculate the reason of the secondary failure. The 1-year IFX drug survival, which included the discontinuation of secondary failure and side effects, was 79.41% in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic backgrounds including HLA were not assessed. 20 There were no data of serum level of TNF and of anti-IFX antibody to speculate the reason of the secondary failure. The 1-year IFX drug survival, which included the discontinuation of secondary failure and side effects, was 79.41% in this study (data not shown).…”
Section: Discussionmentioning
confidence: 99%